DAMPAK ANTESEDEN DIMENSI KUALITAS TERHADAP KEPUASAN PENGGUNA SISTEM E-FILING (STUDI EMPIRIS PADA WAJIB PAJAK UMKM DI KABUPATEN GIANYAR BALI) - I Made Purba Astakoni; Ida bagus Swaputra; Kadek Ryan Putra Richadinata; Yenny Verawati; Ni Made Satya Utami (KRISNA: Kumpulan Riset Akuntansi, 2022)
This study aims to empirically examine the effect of information quality, system quality and service quality on user satisfaction of e-filing systems. The research model offered tries to lift the first and second order models in testing the measurement of existing indicators. Samples were taken from the entire population of micro, small and medium enterprises (MSMEs) taxpayers spread over seven sub-districts in Gianyar Regency, as many as 128 MSMEs. The data analysis technique in this research uses SEM-PLS analysis to test the research hypothesis. In this study PLS is considered appropriate to test the model in developing the existing theory. The results of the overall model evaluation based on the value of R-Square (R2), Q-Square Predictive Relevance (Q2) and Goodness of Fit (GoF) that the model is declared good. The results of testing the first hypothesis indicate that the quality of information has a significant positive effect on user satisfaction of the e-filing system. The results of testing the second hypothesis indicate that the quality of the system has no effect on user satisfaction of the e-filing system. The results of testing the third hypothesis indicate that service quality has a significant positive effect on user satisfaction of the e-filing system.